Penerapan Lubang Biopori Pada Pemukiman Perkotaan sebagai Solusi Mitigasi Banjir di Kelurahan Jatiwaringin - Sari Ningsih; Kiky Setyawati; Pretty Failasufa Aziza (P3M FIA UNKRIS, 2023)
The problem of organic waste and flood risk is a major issue in Jatiwaringin Village. A community service activity conducted by the Faculty of Administrative Sciences, Krisnadwipayana University, aimed to raise public awareness and provide practical skills in organic waste management through the creation of biopores as a flood mitigation solution. This activity was carried out in collaboration with approximately 40 participants from Jatiwaringin Village, consisting of representatives from each neighborhood unit (RW). The implementation method included outreach on the benefits of biopores, hands-on training on biopore construction, and mentoring in the participants' homes. The results of the activity showed a significant increase in participants' understanding of biopores and their benefits. Furthermore, there was increased community participation in biopore construction in their respective neighborhoods. It can be concluded that biopore education and training effectively increased public awareness and provided practical skills in organic waste management while reducing flood risk at the village level.